Foundations of education : - Travers, Paul D. (Allyn and Bacon, 1995)
Offers future teachers a view of the world of teaching. The book asserts that theory and practice are best correlated when perspectives from both formal levels of education are incorporated into teacher education. The chapters are free of unnecesary jargon, designed to be useful for beginning students in professional education, and are adaptable to varied teaching.